احکام القرآن للجصاص میں قواعد فقہیہ اور قواعد اصولیہ کا تحقیقی مطالعہ - Hafiz Muazzum Shah; Dr Ghulam Hussain Khan; Dr.Haris Saleem Khan (الضحی, 2021)
Imam Abu Bakar AL Jassas Al Razi is one of the Prominent exegetes and legal theorists who occupy a distinguished place among Hanafi jurists. He was born in 305 AH and remained a famous Hanafi Legal expert in Baghdad. He wrote a commentary on the Qur'an entitled Ahkam al-Qur'an (The Legal Rulings of the Qur'an) with emphasis on the verses having legal importance. This commentary deals with the deduction of juristic injunctions and rulings from the noble Qur’an in a systematic and methodical way. This research is basically a discussion on AL-Jassas's methodology of deduction of rulings from the Holy Quran with special reference to the principles of Islamic Jurisprudence he used in his commentary on the Quran. The research is a focused study of some important Qawaed Usooliyyah he has applied during his discussion on the various rulings he derives from the Quranic Verses.  This study proceeds with an introduction and short biography of Imam Abubakar Al-Jassas followed by an explanation of the general methodology he adopted in His Tafseer. The second part of the study focuses on some important Qawaed Usooliyyah applied and discussed by the AL-Jassas. The last part of this study consists of the conclusion and findings of this article. The study found that Al-Jassas has discussed most of the Qawaed Usooliyyah either explicitly or explicitly and applied them in the process of deduction of rulings from the Holy Quran. He has also used some Qawaed Usooliyyah which he derives from the different verses of the Quran.